2005
DOI: 10.1172/jci22873
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 clade promoters strongly influence spatial and temporal dynamics of viral replication in vivo

Abstract: Although the primary determinant of cell tropism is the interaction of viral envelope or capsid proteins with cellular receptors, other viral elements can strongly modulate viral replication. While the HIV-1 promoter is polymorphic for a variety of transcription factor binding sites, the impact of these polymorphisms on viral replication in vivo is not known. To address this issue, we engineered isogenic SIVmac239 chimeras harboring the core promoter/enhancer from HIV-1 clades B, C, and E. Here it is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 53 publications
4
28
1
Order By: Relevance
“…Alternatively, PTX-B could downregulate AP-1 mediated activation of the intragenic gag enhancer (48,60), previously suggested to be induced by stimuli, such as IL-6, in combination with TNF-␣ or glucocorticoids (38,49). In this regard, our findings on the levels of luciferase expression driven by LTRs after IL-6 stimulation add to previous reports on biological differences among the different HIV clades, which are determined in part by differences in the composition of the LTR promoter (52,(77)(78)(79)(80). Thus, differences in the composition of transcription factor binding sites may provide each clade with a promoter responding in a unique matter to cellular activation pathways.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, PTX-B could downregulate AP-1 mediated activation of the intragenic gag enhancer (48,60), previously suggested to be induced by stimuli, such as IL-6, in combination with TNF-␣ or glucocorticoids (38,49). In this regard, our findings on the levels of luciferase expression driven by LTRs after IL-6 stimulation add to previous reports on biological differences among the different HIV clades, which are determined in part by differences in the composition of the LTR promoter (52,(77)(78)(79)(80). Thus, differences in the composition of transcription factor binding sites may provide each clade with a promoter responding in a unique matter to cellular activation pathways.…”
Section: Discussionsupporting
confidence: 80%
“…One to three NF-B binding sites may be present in the enhancer regions of SIV or different HIV-1 subtypes (9,38,46). We hypothesized that the number of such sites in the viral LTR may affect viral replication and virulence.…”
Section: Resultsmentioning
confidence: 99%
“…Two RhM, 97R0350 and 98R0026, were intravenously coinoculated with 100 50% tissue culture infectious doses (TCID 50 ) of each cell-free STR-B, STR-C and STR-E chimeras. CD4 and CD8 T lymphocytes were quantified by flow cytometry as described previously [17]. Faeces samples were placed in sterile tubes and immediately frozen at À808C.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that HIV-1 clade promoters strongly influence spatial and temporal dynamics of viral replication in vivo [17]. The SIVmac239 clone was engineered in which it was possible to freely exchange the viral promoter without altering nef (clone named STR for short terminal repeat).…”
Section: Introductionmentioning
confidence: 99%